Analysis of Chemistry Multiple-Choice Test Items on the Periodic Table and Periodic Properties of Elements at Srijaya Negara Senior High School - Revnika Fethya; Effendi Nawawi (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
This study aims to evaluate the quality of multiple-choice test items related to the Periodic Table of Elements and Periodic Properties of Elements material at SMA Srijaya Negara. A descriptive quantitative approach was employed using documentation, observation, and interview techniques. The sample consisted of test items that had been administered to students. The results indicate that several questions did not meet the expected quality criteria. Revisions and improvements in teachers’ competence in developing assessment instruments are necessary. Improving test items and enhancing teacher professionalism are essential steps to improve the quality of evaluation.